Mechanical properties of polypropylene composites reinforced with alkaline treated pineapple leaf fibre from Josapine cultivar - Selamat, Mohd Zulkefli; Ahadlin, Mohd Daud; YAAKOB, MOHD YUHAZRI; Azma, Putra; Sivakumar, Dhar Malingam (Universiti Malaysia Pahang, 2016)
This study investigates the mechanical properties of high impact polypropylene composite reinforced with pineapple leaf fibre from the Josapine cultivar as a function of fibre loading. PLF was extracted by using a pineapple leaf fibre machine and then an alkaline treatment was conducted to enhance the properties. Samples of the composite were fabricated with 100 mm fibre length with five different fibre loadings of PLF (30, 40, 50, 60 and 70 wt%). The fabrication was made by a compression moulding technique with unidirectional fibre orientation. Related tests such as tensile, hardness and density tests were conducted to determine the effect of fibre loading. The experimental data showed that the composite with the 60 wt% fibre loading offered the highest value of tensile strength, which was about 309%, and the Young’s modulus was about 540% compared to 0 wt% of PLF loading. Meanwhile, the hardness and density of the PLF/PP composites showed very similar values, with small increments from 30 wt% up to 70 wt% PLF loading compared to 0 wt% of PLF loading. The highest values are 65.38 Shore-D and 1.002 g/cm³ respectively. The results also revealed that PLF from the Josapine cultivar with alkaline treatment greatly influences the mechanical properties of PLF/PP composite.